Animals in underwear ABC - Parr, Todd (LB kids / Hachette Book Group, 2013)
Presents the letters of the alphabet with animals wearing different types of underwear representing each letter, from "A" for alligator and "E" for elephant to "W" for walrus and "Z" for zebra